Integrasi Perspektif Psikologi Perilaku Sosial dan Humanistik dalam Perumusan Kebijakan Publik yang Responsif terhadap Kebutuhan Masyarakat - Regiena Sari (Jurnal Ragam Pengabdian, 2026)
This study examines the importance of integrating social behavioral psychology and humanistic perspectives in the formulation of public policies that are responsive to societal needs. Many public policies today fail to reflect the real needs of society because they prioritize technocratic approaches without considering social and psychological factors. The objective of this research is to explore how these two perspectives can enhance the relevance and effectiveness of public policies. The methodology employed is library research, gathering primary data from literature on public policy theory, social behavioral psychology, and humanistic perspectives. Secondary data includes previous research findings on the topic. The results of the study indicate that policies integrating social behavioral and humanistic theories are more likely to be accepted by the public, increase public participation, and promote sustainable social change. However, the main challenges in implementation lie in the dominance of technocratic approaches and resistance to integrating psychological perspectives. The study concludes that responsive public policies require a deep understanding of social psychology and humanistic principles, which can strengthen the effectiveness and fairness of such policies